2020
DOI: 10.1021/acs.langmuir.9b03779
|View full text |Cite
|
Sign up to set email alerts
|

Structure–Activity Relationships of Hydroxyapatite-Binding Peptides

Abstract: Elucidating the structure−activity relationships between biomolecules and hydroxyapatite (HAP) is essential to understand bone mineralization mechanisms, develop HAP-based implants, and design drug delivery vectors. Here, four peptides identified by phage display were selected as model HAP-binding peptides (HBPs) to examine the effects of primary amino acid sequence, phosphorylation of serine, presence of charged amino acid residues, and net charge of the peptide on (1) HAP-binding affinity, (2) secondary conf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 39 publications
2
11
0
Order By: Relevance
“…On the basis of bioinformatics, molecular dynamics, and metadynamics calculations, Zhao et al concluded that the charge density of the peptide primarily controls the binding affinity to the surface, while the secondary structure plays a minor role . More recently, on the basis of CD, binding affinity, and mineral morphology analyses, Ling et al concluded that the HAp-binding affinity is correlated with inhibition of transformation to crystalline HAp and formation of plate-like particles instead of needle-like particles . The findings of Ling et al agree well with a previously studied phage display selected HAp-binding peptide by Gungormus et al They showed that a peptide with strong binding affinity to HAp (HABP1) results in larger early spherical ACP particles and a predominantly plate-like particle morphology.…”
Section: Results and Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…On the basis of bioinformatics, molecular dynamics, and metadynamics calculations, Zhao et al concluded that the charge density of the peptide primarily controls the binding affinity to the surface, while the secondary structure plays a minor role . More recently, on the basis of CD, binding affinity, and mineral morphology analyses, Ling et al concluded that the HAp-binding affinity is correlated with inhibition of transformation to crystalline HAp and formation of plate-like particles instead of needle-like particles . The findings of Ling et al agree well with a previously studied phage display selected HAp-binding peptide by Gungormus et al They showed that a peptide with strong binding affinity to HAp (HABP1) results in larger early spherical ACP particles and a predominantly plate-like particle morphology.…”
Section: Results and Discussionsupporting
confidence: 57%
“…41 More recently, on the basis of CD, binding affinity, and mineral morphology analyses, Ling et al concluded that the HAp-binding affinity is correlated with inhibition of transformation to crystalline HAp and formation of plate-like particles instead of needle-like particles. 42 The findings of Ling et al agree well with a previously studied phage display selected HAp-binding peptide by Gungormus et al 36 They showed that a peptide with strong binding affinity to HAp (HABP1) results in larger early spherical ACP particles and a predominantly plate-like particle morphology. However, when considering a structure−function relationship for a peptide, binding to mineral surface and promotion/inhibition of mineralization should be considered as related but separate functions.…”
Section: ■ Materials and Methodsmentioning
confidence: 94%
“…In fact, both the Arg and Asp side chains of the RGD peptide are likely to participate in the binding of the Hap surface to the Fmoc-FF/S/RGD hydrogel. Molecular dynamics simulations suggest that electrostatic interactions play a dominant role in the binding of peptides and proteins to Hap surfaces and that charged groups such as carboxylate, amine or guanidine may interact with the calcium, phosphate and hydroxide ions on the Hap crystal lattice [58] , [59] , [60] . This could explain the increased mechanical properties (raise of G') observed for Fmoc-FF/S/RGD incorporating Hap compared to the other hydrogels, as shown in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…This process consists of multiple stages during which several intermediate calcium phosphate species are formed, leading to the formation of crystalline HAp. This process is kinetically favorable to classical crystal nucleation, and its precursors are thermodynamically stable . However, the process is not fully understood …”
Section: Introductionmentioning
confidence: 99%